Health experiences of child migrants in the Western Pacific region. Issue 1 (1st January 2022) - Spencer, Grace; Smith, Melody; Hoare, Karen; Fouché, Christa; Thompson, Jill
ABSTRACT: Migration is a key social determinant of health affecting children's life chances and health outcomes. Yet, relatively little is known about young migrants' own health experiences. This paper reports findings from a systematic review examining the health experiences of children who migrated in the Western Pacific region. A systematic search of the peer-reviewed literature from 2007–17 was conducted using MEDLINE, EMBASE, PsycINFO, CINAHL, Cochrane Database of Systematic Reviews, Web of Science, ASSIA and IBSS. Included articles reported data generated with children up to 18 years and who had migrated across international borders to the Western Pacific region (predominantly Australasia). The Mixed Methods Appraisal Tool was used to assess study quality. Eleven of 499 articles identified were included in the review and focused on three areas: diet and body size; mental health; and social integration. The review exposes the paucity of research on the health experiences of child migrants in the Western Pacific region. More child-centred research that examines the health-related impacts of migration on young people, and from their own perspectives, is urgently needed.